Setting health priorities in research: an african perspective - Amondi Wasunna, Angela (Acta Bioethica, 2004)
There is much biomedical and epidemiological research taking place in Africa today. This research is both horizontal (involving local researchers and regional research institutions) and vertical (involving international research sponsors and collaborators). Research is the necessary pathway for any biomedical innovation designed to improve health and, in most cases, such research requires the use of human beings as research participants. Research participants cannot however, be viewed in isolation; they live in communities has become almost a mantra in the research ethics world to say that communities must benefit from positive research outcomes. This ethical rule is important; however, my paper will focus on community involvement prior to the actual research being carried out. Using African examples as case studies, I will examine the extent to which communities are involved in setting the health research agenda for their members and whether or not they are included in priority setting activities. Research being undertaken in several African communities may indeed address health problems in that community; however, how high are those problems in the list of health priorities for that particular community? Are other important health problems being neglected? While much has been said about provision of treatment shown to be successful after research to the wider community, not enough has been said about who decides what research is important for the community before such research is carried out.. This begs the question: how do communities benefit from research activities taking place within their own locales? It